HP-aZIF-Tar-Au sensor, preparation method thereof and application of HP-aZIF-Tar-Au sensor in detection of human sweat tyrosine
By using HP-aZIF@Tar@Au sensor, combined with SERS technology and MOFs, the problem of difficult to detect tyrosine in sweat with high sensitivity in the prior art is solved, and the ultra-sensitive specific detection of tyrosine is achieved, with the detection limit reaching 10-8M.
Patent Information
- Application Number
- CN202411469675.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-21
AI Technical Summary
It is difficult for the prior art to effectively combine SERS technology with MOFs to achieve high sensitivity and specific detection of tyrosine molecules in sweat.
The HP-aZIF@Tar@Au sensor is used, which consists of AAO substrate and the loaded HP-aZIF@Tar@Au composite material. The composite material is composed of HP-ZIF-67, HAuCl4 and L-tartaric acid. It is prepared by physical deposition method to achieve ultra-sensitive specific detection of tyrosine.
It realizes rapid identification of tyrosine in human sweat, has excellent sensitivity and selectivity, and can effectively distinguish tyrosine from other interfering substances in complex biological environments, and achieves high-precision detection, with a detection limit of 10-8M.
Smart Images

Figure CN119555658A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sensors, and in particular relates to a HP-aZIF@Tar@Au sensor and a preparation method thereof, and an application thereof in detecting tyrosine in human sweat. Background Art
[0002] Sweat is rich in biomarkers and metabolites that can provide valuable insights into an individual's health, athletic performance, and potential disease risk. Diseases such as albinism and melanoma can lead to abnormal expression of tyrosine in sweat, so detecting the content of tyrosine in sweat has important biomedical value.
[0003] Surface enhanced Raman scattering (SERS) is a non-destructive molecular detection technology that reflects the vibration energy and rotation energy information of molecular bonds. It is a "fingerprint" spectrum that can specifically identify molecules. When the target detection molecules are adsorbed onto certain rough metal surfaces (such as gold, silver, copper, etc.), their Raman scattering intensity will increase by 10 4 ~10 6 This technology has the advantages of high sensitivity, small sample amount, simple pretreatment, no sample destruction and no interference in the simultaneous detection of multiple analytes.
[0004] Metal-organic frameworks (MOFs) are versatile and customizable materials composed of metal ions and organic ligands arranged in a crystal structure. They have a wide range of applications in various scientific fields, including chemistry, biology, and materials science. One important application of MOFs is the targeted detection of small molecules present in sweat. ZIF-67 is a metal-organic framework material (MOF) with multiple advantages such as high selectivity, high sensitivity, good stability, good controllability, and versatility, and is a research hotspot in the field of small molecule monitoring in sweat.
[0005] However, combining SERS technology with MOFs to achieve effective capture and detection of tyrosine molecules in sweat requires the development of new integrated strategies and technologies. To this end, the present invention proposes a HP-aZIF@Tar@Au sensor and its preparation method and application in detecting tyrosine in human sweat. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a HP-aZIF@Tar@Au sensor and a preparation method thereof and an application thereof in detecting tyrosine in human sweat.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] One of the technical solutions of the present invention:
[0009] A HP-aZIF@Tar@Au sensor comprises an AAO (anodized aluminum oxide) substrate and an HP-aZIF@Tar@Au composite material loaded on the surface of the AAO substrate, wherein the raw materials for preparing the HP-aZIF@Tar@Au composite material include HP-ZIF-67, HAuCl 4 and L-tartaric acid.
[0010] Furthermore, the HP-ZIF-67 is a ZIF-67 with a porous structure, "HP" stands for hierarchical porosity, and the metal salt used to prepare HP-ZIF-67 is Co(NO 3 ) 2 6H 2 O, the ligand is 2-methylimidazole.
[0011] Furthermore, the loading amount of the HP-aZIF@Tar@Au composite material on the AAO substrate is 0.075 mg / cm 2 .
[0012] The second technical solution of the present invention:
[0013] A method for preparing the HP-aZIF@Tar@Au sensor comprises the following steps:
[0014] HP-ZIF-67 was dispersed in solvent and then HAuCl was added 4 The solution was mixed and stirred, the product was centrifuged and redispersed with solvent, and NaBH 4 The solutions were mixed and stirred in an ice-water bath to obtain a mixed solution, which was purified by centrifugation and dried to obtain HP-ZIF-67@Au;
[0015] The HP-ZIF-67@Au and L-tartaric acid are mixed and ground, and then refluxed in toluene, cooled, centrifuged and dried to obtain a HP-aZIF@Tar@Au composite material;
[0016] The HP-aZIF@Tar@Au composite material was dispersed with DMF and then dropped onto a hydrophilically treated AAO substrate to obtain the HP-aZIF@Tar@Au sensor.
[0017] Furthermore, the solvent is anhydrous ethanol and deionized water, and the volume ratio of the anhydrous ethanol to the deionized water is 1:2.
[0018] Furthermore, the HP-ZIF-67 and HAuCl 4 The molar ratio of Au in the mixed solution is 2:1. 3+ With NaBH 4 NaBH in solution 4The molar ratio is 3:20.
[0019] Furthermore, the HAuCl 4 The concentration of the solution is 0.025 M, and the NaBH 4 The concentration of the solution is 0.1M.
[0020] Furthermore, the molar ratio of the HP-ZIF-67@Au to L-tartaric acid is 1:1.2.
[0021] Furthermore, the concentration of the HP-aZIF@Tar@Au composite material after being dispersed in DMF is 2 mg / mL.
[0022] Furthermore, HP-ZIF-67 was dispersed in solvent and HAuCl was added. 4 The solution was mixed and stirred at room temperature for 3 h, and NaBH 4 The solution was stirred in an ice-water bath for 5 h.
[0023] Furthermore, the AAO substrate is hydrophilically treated with 2-aminoterephthalic acid.
[0024] Furthermore, the AAO substrate has a diameter of 390 nm and a thickness of 40 μm.
[0025] The third technical solution of the present invention:
[0026] An application of the HP-aZIF@Tar@Au sensor in detecting tyrosine in human sweat.
[0027] Furthermore, the tyrosine in human sweat attached to the surface of the HP-aZIF@Tar@Au sensor was measured by Raman spectrometry, and the detection limit reached 10 -8 M.
[0028] Compared with the prior art, the present invention has the following advantages and technical effects:
[0029] The HP-aZIF@Tar@Au sensor provided by the present invention adopts a physical deposition preparation method, which is not only simple but also efficient. The HP-aZIF@Tar@Au sensor is mainly used for ultra-sensitive and specific detection of tyrosine in human sweat, and the HP-aZIF@Tar@Au sensor can realize rapid recognition of tyrosine in a complex biological environment, with excellent sensitivity and selectivity. In practical applications, tyrosine can be effectively distinguished from other interfering substances to achieve high-precision detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0031] Figure 1 This is the SEM characterization image of HP-ZIF-67@Au prepared in Example 1;
[0032] Figure 2 This is a SEM characterization image of the HP-aZIF@Tar@Au composite material prepared in Example 2;
[0033] Figure 3 XRD patterns of the HP-ZIF-67@Au prepared in Example 1 and the HP-aZIF@Tar@Au composite material prepared in Example 2;
[0034] Figure 4 Raman spectra of SERS detection of tyrosine at different concentrations by the HP-aZIF@Tar@Au sensor prepared in Example 3;
[0035] Figure 5 Raman spectra of the HP-aZIF@Tar@Au sensor prepared in Example 3 for SERS detection of 9 amino acids;
[0036] Figure 6 The HP-aZIF@Tar@Au sensor pair prepared in Example 3 and Comparative Example 3 is 10 -5 Raman test result diagram of M-tyrosine;
[0037] Figure 7 The HP-aZIF@Tar@Au sensor pair 10 prepared in Example 3 and Comparative Example 4 -5 Relative standard deviation (RSD) graph of 20 test points of M-tyrosine. DETAILED DESCRIPTION
[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0039] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0043] The embodiment of the present invention provides a HP-aZIF@Tar@Au sensor, comprising an AAO (anodized aluminum oxide) substrate and an HP-aZIF@Tar@Au composite material supported on the surface of the AAO substrate, wherein the raw materials of the HP-aZIF@Tar@Au composite material include HP-ZIF-67, HAuCl 4 and L-tartaric acid.
[0044] In a preferred embodiment of the present invention, the loading amount of the HP-aZIF@Tar@Au composite material on the AAO substrate is 0.075 mg / cm 2 .
[0045] In a preferred embodiment of the present invention, the HP-ZIF-67 is ZIF-67 with a porous structure, "HP" stands for hierarchical porosity, and the metal salt for preparing HP-ZIF-67 is Co(NO 3 ) 2 6H 2 O, ligand is 2-methylimidazole, which was purchased from Maclean Co., Ltd.
[0046] The embodiment of the present invention also provides a method for preparing the HP-aZIF@Tar@Au sensor, comprising the following steps:
[0047] HP-ZIF-67 was dispersed in solvent and then HAuCl was added 4 The solution was mixed and stirred, the product was centrifuged and redispersed with solvent, and NaBH4 The solutions were mixed and stirred in an ice-water bath to obtain a mixed solution, which was purified by centrifugation and dried to obtain HP-ZIF-67@Au;
[0048] The HP-ZIF-67@Au and L-tartaric acid are mixed and ground, and then refluxed in toluene, cooled, centrifuged and dried to obtain a HP-aZIF@Tar@Au composite material;
[0049] The HP-aZIF@Tar@Au composite material was dispersed with DMF and then dropped onto a hydrophilically treated AAO substrate to obtain the HP-aZIF@Tar@Au sensor.
[0050] In a preferred embodiment of the present invention, during the preparation of HP-ZIF-67@Au, the solvents used in the two solvent dispersions are the same, both of which are ethanol aqueous solutions prepared from anhydrous ethanol and deionized water, and the volume ratio of anhydrous ethanol to deionized water is 1:2.
[0051] In a preferred embodiment of the present invention, the HP-ZIF-67 and HAuCl 4 The molar ratio of Au in the mixed solution is 2:1. 3+ With NaBH 4 NaBH in solution 4 The molar ratio is 3:20.
[0052] In a preferred embodiment of the present invention, the HAuCl 4 The concentration of the solution is 0.025 M, and the NaBH 4 The concentration of the solution is 0.1M.
[0053] In a preferred embodiment of the present invention, the molar ratio of the HP-ZIF-67@Au to L-tartaric acid is 1:1.2. The mixed grinding is preferably performed using an agate mortar, and the grinding time is 15 minutes.
[0054] In a preferred embodiment of the present invention, a washing step is further included after centrifugation, and specifically ethanol is used to wash the product; and the drying is specifically vacuum drying at 60° C. overnight.
[0055] In a preferred embodiment of the present invention, the concentration of the HP-aZIF@Tar@Au composite material after being dispersed in DMF is 2 mg / mL.
[0056] In a preferred embodiment of the present invention, HP-ZIF-67 is dispersed in a solvent and then HAuCl is added. 4 The solution was mixed and stirred at room temperature for 3 h, and NaBH 4 The solution was stirred in an ice-water bath for 5 h.
[0057] In a preferred embodiment of the present invention, the AAO substrate is hydrophilized by 2-aminoterephthalic acid. The specific treatment steps include: soaking the AAO substrate in a 0.1M 2-aminoterephthalic acid solution for 24 hours, rinsing it with distilled water after the hydrophilic treatment is completed, and drying it at room temperature.
[0058] In a preferred embodiment of the present invention, the AAO substrate has a diameter of 390 nm and a thickness of 40 μm, and is purchased from Shenzhen Topo Precision Film Technology Co., Ltd.
[0059] In the embodiments of the present invention, "room temperature" refers to "25±3°C".
[0060] The technical solution of the present invention is further illustrated by the following embodiments.
[0061] Example 1
[0062] Preparation of HP-ZIF-67@Au:
[0063] 60 mg of porous HP-ZIF-67 was dispersed in 3 mL of anhydrous ethanol and deionized water solution (v / v = 1:2) and ultrasonicated for 10 min to fully disperse. HAuCl was added under stirring. 4 Aqueous solution (5.4 mL, 0.025 M, i.e., HP-ZIF-67 and HAuCl 4 The reaction mixture was stirred at room temperature for 3 h, and then the product was centrifuged (6000 rpm, 5 min) and redispersed in 3 mL of anhydrous ethanol and deionized water solution (v / v=1:2) under ultrasonic treatment, stirred for 5 min, and then placed in an ice-water bath. Then, NaBH was added to the mixture under ice-water bath conditions. 4 An aqueous solution (9 mL, 0.1 M) was added, and the reaction mixture was stirred in an ice-water bath for 5 h. After the reaction was completed, it was centrifuged and purified using anhydrous ethanol in three repeated centrifugation cycles (6000 rpm, 5 min) and dried at 60 °C for 12 h to obtain HP-ZIF-67@Au.
[0064] The SEM characterization image of HP-ZIF-67@Au prepared in Example 1 is shown in Figure 1 ,It can be seen from the figure that Au nanoparticles are evenly distributed on HP-ZIF-67, retaining the porous structure and complete crystal structure of HP-ZIF-67.
[0065] Example 2
[0066] Preparation of HP-aZIF@Tar@Au composites:
[0067] The HP-ZIF-67@Au (1 mmol, 0.28 g) and L-tartaric acid (1.2 mmol, 0.18 g) prepared in Example 1 were ground in an agate mortar for 15 min and then refluxed in toluene for 6 h. Subsequently, the reaction mixture was cooled and centrifuged, and the product was washed with ethanol and dried in vacuum at 60 °C overnight to obtain the HP-aZIF@Tar@Au composite material.
[0068] The SEM characterization image of the HP-aZIF@Tar@Au composite material prepared in Example 2 is shown in Figure 2 ,It can be seen from the figure that after HP-ZIF-67@Au is doped with tartaric acid molecules, HP-aZIF@Tar@Au still retains the multi-level pore structure and undergoes an amorphous transition.
[0069] Example 3
[0070] Preparation of HP-aZIF@Tar@Au sensor:
[0071] The AAO substrate was hydrophilized with 2-aminoterephthalic acid, and the specific process was as follows:
[0072] The AAO substrate was immersed in a 0.1 M 2-aminoterephthalic acid solution for 24 h. After the hydrophilic treatment was completed, it was rinsed with distilled water, dried at room temperature, and set aside.
[0073] The HP-aZIF@Tar@Au composite material prepared in Example 2 was dispersed in DMF to obtain a mixture with a concentration of 2 mg / mL. 50 μL of the mixture was dropleted onto an AAO substrate (pore size 390 nm, thickness 40 μm) hydrophilically treated with 2-aminoterephthalic acid to increase the loading of the HP-aZIF@Tar@Au composite material on the AAO substrate to 0.075 mg / cm 2 , and obtained the HP-aZIF@Tar@Au sensor.
[0074] The XRD spectra of the HP-ZIF-67@Au prepared in Example 1, the HP-aZIF@Tar@Au composite material prepared in Example 2, and the raw material HP-ZIF-67 of Example 1, and the XRD standard chart of Au and ZIF-67 are shown in Figure 3 , it can be seen that HP-ZIF-67 in the HP-aZIF@Tar@Au composite material is converted into amorphous MOF.
[0075] The Raman spectrometer was used to measure the Raman test of tyrosine (Try) in human sweat attached to the surface of the HP-aZIF@Tar@Au sensor prepared in Example 3. A 50× objective lens was used, the laser power was 0.15 mW, the integration time was 10 seconds, and the number of integrations was 1. The Raman spectra of the HP-aZIF@Tar@Au sensor prepared in Example 3 for SERS detection of tyrosine at different concentrations are shown in Figure 2. Figure 4 It can be seen that the detection limit reaches 10 -8 M.
[0076] The HP-aZIF@Tar@Au sensor prepared in Example 3 was used to perform SERS detection on 12 kinds of amino acids, and the Raman spectra were shown in Figure 5 , proving that the HP-aZIF@Tar@Au sensor has a specific detection function for tyrosine. The present invention achieves the specific recognition of Tyr in complex sweat through the difference in adsorption energy between different amino acids and tartaric acid.
[0077] Comparative Example 1
[0078] The method provided by the patent with application number 201610619910.7 has a detection limit of 3.0×10 -5 mol / L.
[0079] Comparative Example 2
[0080] The SERS detection limit (LOD) of the microneedle SERS sensor used for in situ detection of tyrosinase in the patent with application number 202311113388.1 is 0.01U / m.
[0081] Comparative Example 3
[0082] The preparation of HP-ZIF-67@Au was the same as in Example 1;
[0083] The preparation of HP-aZIF@Tar@Au composite material was the same as in Example 2, except that HP-ZIF-67@Au (1 mmol, 0.28 g) and L-tartaric acid (0.6 mmol, 0.09 g) were ground in an agate mortar;
[0084] The preparation method of HP-aZIF@Tar@Au sensor is the same as that in Example 3.
[0085] Comparative Example 4
[0086] The preparation of HP-ZIF-67@Au was the same as in Example 1;
[0087] The preparation of HP-aZIF@Tar@Au composite material was the same as in Example 2;
[0088] The preparation method of the HP-aZIF@Tar@Au sensor was the same as that of Example 3, except that the loading amount of the HP-aZIF@Tar@Au composite material on the AAO substrate was 0.045 mg / cm 2 .
[0089] The detection and uniformity performance of the sensors prepared in Example 3 and Comparative Examples 3-4 were tested. The HP-aZIF@Tar@Au sensors prepared in Example 3 and Comparative Example 3 were tested for 10 -5 The Raman test results of M tyrosine are shown in Figure Figure 6 , the HP-aZIF@Tar@Au sensor prepared in Example 3 and Comparative Example 4 is 10 -
[0090] 5 The relative standard deviation (RSD) of 20 test points of M-tyrosine is shown in the figure Figure 7 ,Depend on Figure 6 , Figure 7 It can be seen that reducing the amount of tartaric acid added and changing the loading amount of HP-aZIF@Tar@Au composite material on the AAO substrate will lead to a decrease in the test uniformity performance of the sensor.
[0091] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A HP-aZIF@Tar@Au sensor, characterized in that: The invention comprises an AAO substrate and a HP-aZIF@Tar@Au composite material loaded on the surface of the AAO substrate. Raw materials for preparing the HP-aZIF@Tar@Au composite material comprise HP-ZIF-67, HAuCl4 and L-tartaric acid.
2. The HP-aZIF@Tar@Au sensor according to claim 1, characterized in that: The loading amount of the HP-aZIF@Tar@Au composite material on the AAO substrate is 0.075 mg / cm 2 .
3. A method for preparing the HP-aZIF@Tar@Au sensor according to any one of claims 1 to 2, characterized in that: The following steps are involved: HP-ZIF-67 was dispersed with a solvent, and then HAuCl4 solution was added and mixed and stirred. The product was centrifuged and then dispersed with a solvent again, and NaBH4 solution was added and mixed and stirred in an ice-water bath to obtain a mixed solution, which was purified by centrifugation and dried to obtain HP-ZIF-67@Au. The HP-ZIF-67@Au and L-tartaric acid are mixed and ground, and then refluxed in toluene, cooled, centrifuged and dried to obtain a HP-aZIF@Tar@Au composite material; The HP-aZIF@Tar@Au composite material was dispersed with DMF and then dropped onto a hydrophilically treated AAO substrate to obtain the HP-aZIF@Tar@Au sensor.
4. The method for preparing the HP-aZIF@Tar@Au sensor according to claim 3, characterized in that: The molar ratio of HP-ZIF-67 to HAuCl4 is 2:
1. 3+ The molar ratio of NaBH4 to NaBH4 in the NaBH4 solution is 3:
20.
5. The method for preparing the HP-aZIF@Tar@Au sensor according to claim 4, characterized in that: The concentration of the HAuCl4 solution is 0.025M, and the concentration of the NaBH4 solution is 0.1M.
6. The method for preparing the HP-aZIF@Tar@Au sensor according to claim 3, characterized in that: The molar ratio of the HP-ZIF-67@Au to L-tartaric acid is 1:1.
2.
7. The method for preparing the HP-aZIF@Tar@Au sensor according to claim 3, characterized in that: The concentration of the HP-aZIF@Tar@Au composite material after being dispersed in DMF is 2 mg / mL.
8. The method for preparing the HP-aZIF@Tar@Au sensor according to claim 3, characterized in that: After HP-ZIF-67 was dispersed in a solvent, HAuCl4 solution was added, mixed and stirred at room temperature for 3 h, and NaBH4 solution was added and mixed and stirred in an ice-water bath for 5 h.
9. The method for preparing the HP-aZIF@Tar@Au sensor according to claim 3, characterized in that: The AAO substrate is hydrophilically treated with 2-aminoterephthalic acid.
10. Use of the HP-aZIF@Tar@Au sensor according to claim 1 in detecting tyrosine in human sweat, characterized in that: The tyrosine in human sweat attached to the surface of the HP-aZIF@Tar@Au sensor was measured by Raman spectroscopy with a detection limit of 10 -8 M.
Citation Information
Patent Citations
SERS substrate with hierarchical pore metal organic framework-noble metal composite structure and preparation method and application thereof
CN113984664A
Ratio-type detection method for histamine by using SERS active substrate of MOF-based composite gold nanoflowers
CN115266678A